MON-LB107 Treat: A Randomized Controlled Trial Examining the Effects of Time Restricted Eating on Weight Loss and Metabolic Markers - Lowe, Dylan A (J Endocr Soc, 2020)
Background: Studies indicate that time-restricted eating (TRE) can prevent weight gain and/or lead to weight loss [1,2]. The few human studies to date are small and/or non-randomized [3,4]. This is a prospective and randomized study in humans who are overweight and obese designed to determine if TRE leads to weight loss and to characterize the metabolic effects of TRE. Methods: 140 overweight and obese males and females with a body mass index between 27-43 kg/m(2) were enrolled in the study. 100 participants completed the 12-week protocol. The study was conducted on a custom mobile study app on the Eureka Research Platform. Participants were given a Bluetooth weight scale to use daily, which was connected through the study app. Subjects were randomized to one of two eating plans and received daily reminders about their eating windows through the app. The control group was instructed to eat three structured meals per day. The TRE group was instructed to eat ad libitum from 12:00 pm until 8:00 pm and completely abstain from caloric intake from 8:00 pm until 12:00 pm the following day (16h fast:8h eat). Participants who lived within 60 miles of the study site were eligible to undergo extensive in-person metabolic testing. Results: Weight change in the TRE group was -1.3 kg compared to -0.6 kg in the control group (p=0.22). 46 (TRE n=22; control=24) of 50 participants who opted into the “in-person” visits completed all 4 visits. In that cohort, weight change in the TRE group was -1.62 kg compared to -0.57 kg in control (p=0.09). There were no significant differences in the changes in total fat mass, visceral or subcutaneous fat mass, waist or hip measurements, or resting metabolic rate. However, there was a trend towards reduced fat-free mass in the TRE group (-1.10kg) compared to controls (-0.35kg) (p=0.09). There was a significant change in the appendicular fat-free mass index of the TRE subjects compared to controls (p=0.011). This change in appendicular fat-free mass index was not associated with significant differences in strength measures. No changes were observed in plasma ketones, insulin, or glucose between treatment groups. Conclusion: These results indicate that TRE may lead to reductions in body weight in individuals who are overweight or obese. However, the majority of weight loss is attributed to reductions in fat-free mass rather than fat mass. Future analyses will determine if TRE leads to changes in metabolic blood markers or the plasma metabolome. References: 1.Hatori et al. Cell Metab. 2012 Jun 6;15(6):848-60. doi: 10.1016/j.cmet.2012.04.019. Epub 2012 May 17.2. Chaix et al. Cell Metab. 2019 Feb 5;29(2):303-319.e4. doi: 10.1016/j.cmet.2018.08.004. Epub 2018 Aug 30.3.Moro et al. J Transl Med. 2016 Oct 13;14(1):290.4.Wilkinson et al.Cell Metab. 2020 Jan 7;31(1):92-104.e5. doi: 10.1016/j.cmet.2019.11.004. Epub 2019 Dec 5.